(3x+5)(x-11)=0

Simple and best practice solution for (3x+5)(x-11)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3x+5)(x-11)=0 equation:


Simplifying
(3x + 5)(x + -11) = 0

Reorder the terms:
(5 + 3x)(x + -11) = 0

Reorder the terms:
(5 + 3x)(-11 + x) = 0

Multiply (5 + 3x) * (-11 + x)
(5(-11 + x) + 3x * (-11 + x)) = 0
((-11 * 5 + x * 5) + 3x * (-11 + x)) = 0
((-55 + 5x) + 3x * (-11 + x)) = 0
(-55 + 5x + (-11 * 3x + x * 3x)) = 0
(-55 + 5x + (-33x + 3x2)) = 0

Combine like terms: 5x + -33x = -28x
(-55 + -28x + 3x2) = 0

Solving
-55 + -28x + 3x2 = 0

Solving for variable 'x'.

Factor a trinomial.
(-5 + -3x)(11 + -1x) = 0

Subproblem 1

Set the factor '(-5 + -3x)' equal to zero and attempt to solve: Simplifying -5 + -3x = 0 Solving -5 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + -3x = 0 + 5 Combine like terms: -5 + 5 = 0 0 + -3x = 0 + 5 -3x = 0 + 5 Combine like terms: 0 + 5 = 5 -3x = 5 Divide each side by '-3'. x = -1.666666667 Simplifying x = -1.666666667

Subproblem 2

Set the factor '(11 + -1x)' equal to zero and attempt to solve: Simplifying 11 + -1x = 0 Solving 11 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + -11 + -1x = 0 + -11 Combine like terms: 11 + -11 = 0 0 + -1x = 0 + -11 -1x = 0 + -11 Combine like terms: 0 + -11 = -11 -1x = -11 Divide each side by '-1'. x = 11 Simplifying x = 11

Solution

x = {-1.666666667, 11}

See similar equations:

| -5.2m-7.7-1m=-7.9-6.2m-0.2 | | 0.3(0.3(-7)+0.8)=-.3 | | 2x+3=52 | | 3x=x+10+40 | | 2s+3t=27 | | 6x-5=7(x-2) | | 6x-41=25 | | 11x-23=30-8x | | 2+14x-40=11-3x+2x | | (x+3i)(x+3i)=2yi | | 3(2x+1)-4x=2x+3 | | -3=8+4x | | 7x+8y-9=0 | | 3x-6.3=7.5 | | 8(x-5)=4x-4 | | 9+7*2= | | .666x+6=.5x+.25x | | 3x-8=-3x+28 | | 4x-7y+5=0 | | 2x+24=0 | | 3n^2-10n+4=0 | | r=2(3.14)sh | | 9m+(-5m)= | | -6x+16=16 | | 7x^2-45x-343=0 | | 3y-10+y+28=5y+20-3y | | 6x+3x=x+14 | | m=3(1,6) | | 8x^2-59x+40=0 | | 14x^2+7x+14=0 | | 8(w-3)=16 | | |-3|-|2-17|= |

Equations solver categories